Efficacy and safety of hybutimibe in combination with atorvastatin for treatment of hypercholesteremia among patients with atherosclerotic cardiovascular disease risk equivalent: A multicenter, randomized, double-blinded phase III study - Qi, Litong; Chen, Jiyan; Li, Xiaodong; Qi, Xiaoyong; Ding, Chunhua; Chen, Xiaoping; Gu, Xiang; Xiao, Wenliang; Zhao, Shuiping; Dong, Yugang; Zheng, Mingqi; Huang, Kai; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: To evaluate the safety and efficacy of hybutimibe plus atorvastatin for lipid control in hypercholesterolemia patients with atherosclerotic cardiovascular disease risk equivalent. Methods: In this double-blind phase III study, we 1: 1 randomly assigned 255 hypercholesterolemia patients with atherosclerotic cardiovascular disease to receive hybutimibe plus atorvastatin or placebo plus atorvastatin. The primary endpoint was the rate of change of plasma low-density lipoprotein-cholesterol (LDL-C) level at 12 weeks from baseline. The secondary endpoints were plasma total cholesterol (TC), triglyceride (TG), high-density lipoprotein-cholesterol (HDL-C), non-HDL-C, apoprotein (Apo) B, and 2-, 4-, 8-, and 12-week Apo A1 levels change rate and rates of change of plasma LDL-C levels at 2, 4, and 8 weeks from baseline. Results: From April 2016 to January 2018, 128 in the hybutimibe plus atorvastatin group and 125 in the atorvastatin group were included in modified intention-to-treat (mITT) analysis. After 12 weeks of treatment, LDL-C level changed from 2.61 mmol/L(±0.30) at baseline to 2.18 mmol/L (±0.45) in the hybutimibe plus atorvastatin group and from 2.58 (±0.31) mmol/L to 2.40 (± 0.46) mmol/L in the atorvastatin group (P < 0.0001), in mITT. The change rate in the hybutimibe plus atorvastatin group was significantly higher than that in the atorvastatin group (P < 0.0001); the estimated mean rates of change were −16.39 (95% confidence interval: −19.04, −13.74) and −6.75 (−9.48, −4.02), respectively. Consistently, in per-protocol set (PPS) analysis, the rate of change of LDL-C in the hybutimibe plus atorvastatin group was significantly higher than that in atorvastatin group. Significant decreases in the change rates of non-HDL-C, TC, and Apo B at 2, 4, 8, and 12 weeks (all P values < 0.05) were observed for hybutimibe plus atorvastatin, while the differences were not significant for HDL-C, TG, and Apo-A1 (all P values > 0.05). During the study period, no additional side effects were reported. Conclusions: Hybutimibe combined with atorvastatin resulted in significant improvements in LDL-C, non-HDL-C, TC, and Apo B compared with atorvastatin alone. The safety and tolerability were also acceptable, although additional benefits of hybutimibe plus atorvastatin were not observed compared with atorvastatin alone in HDL-C, TG, and Apo-A1.